Phenyl Thiourea as Corrosion Inhibitor for Mild Steel in Strong Hydrochloric Acid - S. Yaro, Aprael; A. Abdulaaima, Dhuha (Iraqi Journal of Chemical and Petroleum Engineering, 2012)
The inhibitive action of Phenyl Thiourea (PTU) on the corrosion of mild steel in strong Hydrochloric acid, HCl, has been investigated by weight loss and potentiostatic polarization. The effect of PTU concentration, HCl concentration, and temperature on corrosion rate of mild steel were verified using 2 levels factorial design and surface response analysis through weight loss approach, while the electrochemical measurements were used to study the behavior of mild steel in 5-7N HCl at temperatures 30, 40 and 50 °C, in absence and presence of PTU. It was verified that all variables and their interaction were statistically significant. The adsorption of (PTU) is found to obey the Langmuir adsorption isotherm. The effect of temperature on the adsorption process showed that the adsorption process is exothermic, spontaneous and represents mixed chemical and physical adsorption for PTU on the metal surface.